Ionospheric effects of an intense geomagnetic storm - Mansilla, Gustavo Adolfo (2007)
An investigation of the response of the mid-high, mid and low latitude critical frequency foF2 to the geomagnetic storm of 15 July 2000 is made. Ground-based hourly foF2 values (proportional to square root of peak electron density of F2-layer) from four chains of ionospheric stations located in the geographic longitude ranges  100 W-350 E, 600 E-1200 E, 1300 E–1700 E, 2500 E–2950 E are used. Relative deviations of foF2 are considered. The main ionospheric effects for the considered storm are: long-duration negative disturbances at mid-high latitudes in summer hemisphere in sectors where the storm onset occurred in the afternoon/night-time hours; short-duration positive disturbances in the summer hemisphere at mid-high latitudes in the pre-sunset hours during the end of main phase-first stage of the recovery; small and irregular negative disturbances in the low latitude winter hemisphere which predominate during the main phase and first part of the recovery, and positive disturbances in both hemispheres at mid-high and mid latitudes prior to the storm onset irrespective of the local time. In addition, the validity of some physical mechanisms proposed to explain the F2 region behaviour during disturbed conditions is considered.